2019
DOI: 10.22146/jpti.32098
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge and Attitude of Integrated Pest Management Farmers Field Schools Alumni toward the Use of Pesticides in Klaten, Central Java, Indonesia

Abstract: The field schools in Indonesia employ an extension alternative model that is considered appropriate to change the habits and behavior of farmers to make them IPM experts in their field. This study was conducted to understand the behavior (knowledge and attitude) of farmers who have joined field schools, i.e. Integrated Pest Management Farmers Field School (IPM-FFS) and Landscape Integrated Pest Management (Landscape IPM), toward the use of pesticides in Klaten, Central Java, Indonesia. The research used a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Effective pest control is a crucial aspect of agricultural productivity and agro-ecosystem sustainability. Farmers play a pivotal role in pest control method implementation, and IPM knowledge can significantly influence their pest control behavior [11][12][13]. This knowledge includes understanding how to integrate and utilize all selective pest control methods, such as employing predators and parasitoids, using pestresistant varieties, adopting appropriate farming techniques, and using pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Effective pest control is a crucial aspect of agricultural productivity and agro-ecosystem sustainability. Farmers play a pivotal role in pest control method implementation, and IPM knowledge can significantly influence their pest control behavior [11][12][13]. This knowledge includes understanding how to integrate and utilize all selective pest control methods, such as employing predators and parasitoids, using pestresistant varieties, adopting appropriate farming techniques, and using pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the farmers had a low attitude towards the danger of the pesticides for farmers' health risk and environmental impact (Atreya et al, 2012). In the comparison of farmers' attitudes toward pest management, the result of (Kusumawardani et al, 2019) concluded that the respondents have the attitude that chemical pesticides have negative effects and lead to air and water pollution. Farmers believed that natural enemies may reduce when applying pesticides on the farm (Mean=3.78).…”
Section: Farmers' Attitudes On Pest Managementmentioning
confidence: 99%